Contemporary Issues in Family Law and Mental Health. - Brock, Michael G. (Charles C Thomas Publisher, LTD, 2008)
Contemporary Issues in Family Law and Mental Health is an original and practical discussion of cutting-edge issues in family relations and the law. Through the prism of family law, and custody disputes in particular, it discusses the basic principles that underlie the proper use of mental health evidence in court and it sets out the proper use of mental health evidence in litigation. The first and most important principal is that forensic mental health practice and procedures must track the legal process, not the other way around. The goal of mental health treatment is fundamentally different.
Keywords: Custody of children -- United States.; Forensic psychology -- United States.; Garde des enfants (Droit) -- États-Unis.; Psychologie légale -- États-Unis.; LAW -- Administrative Law & Regulatory Practice.; Custody of children; Forensic psychology; United States; Law - U.S.; Law - U.S. - General.; Law, Politics & Government.